No Place Like Home? Graduate Migration in Germany - Tina Haussen; Silke Uebelmesser (Center for Economic Studies and ifo Institute (CESifo), 2015)
We empirically analyze sub-national migration of graduates in Germany and its determinants. Based on a longitudinal, representative survey-based dataset of students who graduated in the academic year 2004/2005, we observe the transition to the labor market and previous and subsequent migration patterns. We find that, five years after graduation, about 60% of the graduates are employed in the university state either because they have stayed or returned. Whether or not graduates migrate largely depends on previous migration, job search characteristics and the states' economic conditions. This results in an unbalanced migration of graduates between German states. From a public policy perspective, our analysis provides some rational for correction mechanisms. This paper presents research output of the Ifo Center of Excellence for Migration and Integration Research (CEMIR)
Keywords: I28; H72; H75; J61; 330; graduate migration; higher education funding; longitudinal graduate survey; job changes